Using Quality Benchmarks for Assessing and Developing Undergraduate Programs - Dunn, Dana S. [et al.] (San Francisco Jossey-Bass, 2011)
"Assessing student learning effectively has become a priority in higher education. Faculty and administrators must demonstrate to various constituencies and stakeholders that their programs are effective and that there is correlation between teaching and learning. This book uses selected performance criteria benchmarks to assist undergraduate programs to define their educational missions and goals as well as to document their effectiveness. It helps faculty and administrators use benchmarks not only to assess outcomes of student learning, but to program assessment, evaluate student learning, create meaningful faculty scholarship, ensure quality teaching, and forge connection to the community"--
Include Index and References
Keywords: Education, Higher--Evaluation -- Educational tests and measurements -- Undergraduates